Application of botulinum toxin in the treatment of sialorrhea: Review and clinical perspectives (Research, Society and Development, 2024)
Sialorrhea is a condition defined by excessive saliva production that considerably influences the quality of life of affected patients, especially those with neurological disorders. The general objective of the work is to analyze the efficacy, safety and applicability of botulinum toxin in the treatment of sialorrhea. The present study was developed through a narrative review, using scientific articles available in Portuguese published in the last six years, with free access and available in the Google Scholar and Scielo databases. Hypersalivation is considered a change when it lasts after four years of age, which can cause skin lesions, facilitate suffocation due to aspiration, in addition to interfering with the socialization of the affected individual. Based on this, there is a need for intervention, where botulinum toxin alters salivary production through muscle weakening when applied to the salivary glands. From the study, the use of botulinum toxin appears to be effective and safe as a therapeutic method, standing out compared to other treatment methods that can cause side effects and are considered invasive. Therefore, its clinical application must be based on careful and individual assessments, so that there are no adverse effects and satisfactory results.